Pectin Remodeling and Involvement of AtPME3 in the Parasitic Plant–Plant Interaction, Phelipanche ramosa–Arabidospis thaliana - Cyril Grandjean; Christophe Veronesi; Christine Rusterucci; Charlotte Gautier; Yannis Maillot; Maïté Leschevin; Françoise Fournet; Jan Drouaud; Paulo Marcelo; Luciane Zabijak; Philippe Delavault; Philippe Simier; et al. (Plants, 2024)
Phelipanche ramosa is a root parasitic plant fully dependent on host plants for nutrition and development. Upon germination, the parasitic seedling develops inside the infected roots a specific organ, the haustorium, thanks to the cell wall-degrading enzymes of haustorial intrusive cells, and induces modifications in the host’s cell walls. The model plant Arabidopsis thaliana is susceptible to P. ramosa; thus, mutants in cell wall metabolism, particularly those involved in pectin remodeling, like Atpme3-1, are of interest in studying the involvement of cell wall-degrading enzymes in the establishment of plant–plant interactions. Host–parasite co-cultures in mini-rhizotron systems revealed that parasite attachments are twice as numerous and tubercle growth is quicker on Atpme3-1 roots than on WT roots. Compared to WT, the increased susceptibility in AtPME3-1 is associated with reduced PME activity in the roots and a lower degree of pectin methylesterification at the host–parasite interface, as detected immunohistochemically in infected roots. In addition, both WT and Atpme3-1 roots responded to infestation by modulating the expression of PAE- and PME-encoding genes, as well as related global enzyme activities in the roots before and after parasite attachment. However, these modulations differed between WT and Atpme3-1, which may contribute to different pectin remodeling in the roots and contrasting susceptibility to P. ramosa. With this integrative study, we aim to define a model of cell wall response to this specific biotic stress and indicate, for the first time, the role of PME3 in this parasitic plant–plant interaction.